“L’écomusée n’est pas musée”. Gli ecomusei come laboratori produttori di cultura, territorio e relazione (Altre Modernità, 2011)
In presenting a current project for the implementation of a Landscape Ecomuseum in the Palestinian village of Battir, in West bank, the article explores some aspects of the history and of the theoretical and methodological framework of ecomuseums as emerged within the French movement of the Nouvelle Muséographie from the 1960s, together with other forms of alternative museographical strategies. At the core of the movement – moved by the ambition of starting a process of democratisation of the museal institutions and functions – there were three main ideas: a new conception of heritage, enlarged to encompass all the expressions of human culture and the notions of territory, community and local identity; the need of dispersing the walls of the majority museum to diffuse it on the territory and in the community; a perspective on museums as active engines in the productive process of cultural and social capital, rather than displays of representative projects generated by extra-local hegemonic powers. In rapport to other forms of alternative museums, the ecomuseum, despite representing an intrinsically polymorphous and evolutive reality encompassing a variety of different experiences, is characterised for its central reference and attention to the local dimension, at the environmental, socio-cultural and anthropological level. Rooted in a given territory and designed and animated with the participation of its inhabitants, each ecomuseum is unique since based on the safeguarding and valorisation of a specific social and geographical milieu. In the context of Battir village, characterised by many outstanding traits at the historical, anthropological and landscape level but threatened by the disruptive effects of the Israeli occupation and an ongoing conflict, an ecomuseum of landscape constitutes an important virtuous opportunity for resisting to the destruction of the territory and of the community by promoting and protecting what can be considered a world heritage and a set of shared universal values.